The Application of Bühlmann-Straub Model to the Estimation of Net Premium Rates Depending on the Age of the Insured in the Motor Hull Liability Insurance - Szymańska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
One of the basic variables used in the process of tariff calculation of premiums in motor hull liability insurance is the age of the insured. In this type of insurance offered by insurers operating on the Polish market, this variable is taken into account in the ratemaking by discounts and increases in assigned premium, known as the net premiums rates. The aim of this work is to propose a method of rate estimation of net premiums in the groups of the motor hull liability insurance portfolio of individuals created by the age of the insured. For the premium estimation one of the maximum likelihood models, called the Bühlmann-Straub model was used.